Fortifikasi Fe Minuman Susu Fermentasi Kulit Buah Naga Merah (Hylocereus Polyrhizus) Meningkatkan Berat Badan dan Asupan Protein Pada Remaja Putri Anemia (Jurnal Nutrire Diaita (Ilmu Gizi), 2022)
Background: Iron fortification is a source of iron which can be used to prevent anemia and affect energy and protein metabolism so that it is good for improving nutritional status. Fermented milk is a vehicle for iron which is quite effective accepted by teenagers. Objective: To determine effect of Fe fortification on Fermented Milk of Red Dragon Fruit (Hylocereus polyrhizus) peel enhance body weight and protein intake. Methods: This study was a randomized controlled trial with pre and posttest design with a total 40 anemic adolescent girls. Subjects were divided into 2 groups, control and treatment group. Treatment group was given 100 ml/day fermented milk with 30 mg NaFeEDTA for 3 weeks, while control was given a placebo. Results: Characteristics of two groups at baseline were similar based on age, body weight and protein intake. Based on paired ttest analysis, there was a difference average on body weight before and after intervention in treatment group (p-value=0.000) but not in control group (p-value=0.721). There was a difference average on protein intake before and after intervention on treatment group (p-value=0.000), but not in control group (p-value=0.539). Conclusion: it can enhance weight and protein intake on treatment but not in control group.Keywords: Anemic Adolescent Girls; iron fortification; red dragon fruit peel; enhance body weight and protein